THE IMPACT OF MATHEMATICAL COMPETENCE ON ENGINEERING LEADERSHIP IN THE DIGITAL ERA - Indra Kurniawan R; Giatman; Hassan Maksum; Mukhlidi; Asrul Huda (EDU RESEARCH, 2024)
This research aims to analyze how mathematical proficiency influences the leadership capabilities of engineers, as well as to offer insights to industry practitioners, educators, and policymakers in fostering a generation of future leaders equipped with both technical skills and strategic competencies within the Leadership paradigm of the DU/DI (Industrial and Vocational World). Mathematical principles, encompassing logic, patterns, and structures, have the potential to be applied in strategic decision-making processes, systematic planning, and in-depth analysis. In the context of leadership oriented toward the DU/DI philosophy, a leader's Mathematical Competence can enhance the quality of data-driven decision-making, optimize efficient planning, and improve resource management effectiveness. The method employed in this study is a literature review, utilizing an analytical approach to various relevant scientific sources.The research findings indicate that Mathematical Competence in Vocational Technology Education leadership has a significant impact. These principles enable leaders to optimally allocate resources, minimize inefficiencies, and strengthen resource utilization effectiveness. Additionally, mathematical approaches provide a systematic framework for managing complexity in measured decision-making processes. This study contributes to theoretical insights on the synergy between mathematics and DU/DI leadership, while offering a conceptual foundation to enhance leadership quality by integrating rational and humanistic aspects. The results of this research have theoretical and practical implications, which can serve as a foundation for designing a more effective, rational, and humanistic DU/DI leadership model. To broaden the scope of these findings, further research is recommended, particularly focusing on empirical testing of the effectiveness of mathematical competence in DU/DI leadership contexts and analyzing its long-term impacts in greater depth